Performance Enhancement of Double-Layer Microchannel Heat Sink by Employing Dimples and Protrusions on Channel Sidewalls. (11th May 2022) - Debbarma, Dipak; Pandey, Krishna Murari; Paul, Abhishek
Abstract : High-temperature gradient causes thermal stress and is indirectly responsible for other demerits in nonstacked microchannels. High-temperature gradient is overcome by employing double layers in the heat sink. Utilization of dimple and protrusion in such double-layered sink to enhance overall performance is done in the present numerical study. Before placement of dimples and protrusions on sidewalls of the sink, optimum width and depth of channel have been assessed. Microsinks with the protruded-dimpled bottom layer and microsinks with protruded-dimpled layers are investigated. The parameters such as maximum bottom wall temperature difference (Δ T b ), Nusselt number ratio ( Nu/Nu o ), and thermal performance factor ( η) have been evaluated. The impact of aligned and staggered arrangements of dimple and protrusion is also compared. Deionized water as a coolant for the range of Reynolds number of 89–924 is examined. It has been realized that aligned models offer higher heat transfer coefficient, maximum Nu, and minimum Δ T b, but in terms of overall performance, staggered sinks are superior. The heat sink with both layers protruded and dimpled, showing Nu/Nu o and η of 1.36 and 1.32, respectively, is observed as one of the optimum sinks which offers an excellent lowest Δ T b of 1.48 K.